TATALAKSANA PEMERIKSAAN PASIEN LOW VISION DENGAN KASUS RUBELLA YANG MENGALAMI CEREBRAL PALSY - Candra Hadi Nugroho; Erni Suprihatin; Suci Haryanti (Bajang Institute, 2025)
Introduction Low vision, according to WHO, is a decrease in visual function with visual acuity of less than 6/18 (20/60), including light perception or a visual field of less than 10 degrees from the fixation point, which cannot be maximally corrected with medications, the use of lenses, or even surgery. However, with low vision aids, patients can maximize their remaining vision to carry out certain activities. The success rate of managing low vision greatly depends on the underlying causes and when the initial treatment is provided. Method: The research method used is the qualitative method. This research is a case study conducted at the low vision clinic ARO Kartika in Jakarta. The observation was conducted in November 2023. Result: In this patient, distance vision was assessed using the Worth’s Ivory Ball Test, visual field testing was conducted using simple methods or confrontation, color testing was done by naming the colors on provided colored paper objects, and contrast sensitivity was tested by selecting several objects with high, medium, and low contrast. Conclusion: The management of low vision examinations in children greatly depends on the underlying cause of low vision and is tailored to meet their specific needs.